KEPEMIMPINAN JAWA-ISLAM (YOYOK RIYO SUDIBYO) DALAM PENYELENGARAAN PEMERINTAH DAERAH KABUPATEN BATANG - Sutrisno .; Warsito .; Nunik Retno Herawati (Journal of Politic and Government Studies, 2017)
Leader and leadership is a human natural tendency. National leadership in Indonesia to now has focused more on a leader in harmony with his support community and the plural society that exists. National leadership in Indonesia is also influenced by the many believer of a religion. The research, Leadership of Java-Islam in governance will take the regent with many achievements in the administration of the Batang regency, Yoyok Riyo Sudibyo. The purpose of this study is to know and analyze the leadership of Java-Islam applied by the Regent Yoyok Riyo Sudibyo in the implementation of local government Batang regency.The recearch uses qualitative methods with data collection using in-depth interviews and documents study. Informants in the study are Regent, Vice of Regent, Regional Secretary, Chairman of DPRD, Bureaucracy, Society and Public Figure.Research results explained that the Regent of Yoyok tends to implement leadership of Java-Islam in the administration of Batang Regency. Decision-making in the Regent's tendency is serve like a moon (laku hambeging candra), serve like a fire (laku hambeging dahana),serve like a star (laku hambeging kartika) and serve like an earth (aku hambeging kisma), serve like a wind (laku hambeging samirana) also serve like a water (laku hambeging tirta), while not on serve like a sun (laku hambeging surya) and serve like an ocean (laku hambeging samodra). Then the implementation of leadership by Prophet in terms of shidiq, tabligh and fathonah. His firmness having a relationship with staff and society keep doing serve like a moon (laku hambeging candra), serve like a fire (laku hambeging dahana), serve like an earth (laku hambeging kisma), serve like a wind (laku hambeging samirana), serve like a sun (laku hambeging surya), serve like an ocean (laku hambeging samodra), and serve like a water (laku hambeging tirta) he don’t serve like a star (laku hambeging kartika).  Leadership on Islamic societies tend to do is shidiq, amanah, tabligh and fathonah. Development carried out tends to consider the principle of leadership in Islam. While in the leadership of Java did not leave serve like a water (laku hambeging tirta), serve like an ocean (laku hambeging samodra), serve like a wind (laku hambeging samirana), serve like an earth (laku hambeging kisma), serve like a star (laku hambeging kartika), serve like a fire (laku hambeging dahana and serve like a moon (laku hambeging candra).Keywords: leadership of java, leadership of islam, governance, Regent of Batang